Factors that lead to financial distress of millennials in Malaysia / Nurdini Izzati Shamsuddin - Shamsuddin, Nurdini Izzati (Faculty of Business and Management, 2018)
In this research study will be focus on to understand the factors that lead to financial distress of the millennial in Malaysia. Millennial is the generation of Y that born in 1980s until 1990s. Financial distress happens when the person has a financial problem. Nowadays a lot of young generations that have been declare as bankruptcy around their age. The Star said in January until September 2017 that the number of Malaysians under age 30 years old declared bank-upt from to credit card debts declined to nine individuals compared to 22 last year. This study was focused in internal factor such as saving habits, saving behavior, and financial management that have effect to external factors of financial distress. The objective in this research that to determine of spending behavior, saving habits, and financial management that give an impact to millennial in Malaysia. In this study will use the research method to prove the reliability test using the demographic of respondent and descriptive statistic, correlation analysis, correlation coefflcient and multiple regession analysis. The findings that have found spending behavior and saving habits have a significance relationship toward financial distress while the financial management has no significance relationship toward financial distress. This recommendation for future research to find the external factors that lead to financial disfress and study another group of population. Another recommendation to study the awareness for overcomes the financial distress with seminar, advertisement and social media or speech to gain more knowledge.